The nature of economic costs of biological invasions - Vaissière, Anne-Charlotte; Courtois, Pierre; Courchamp, Franck; Kourantidou, Melina; Diagne, Christophe; Essl, Franz; Kirichenko, Natalia; Welsh, Melissa; Salles, Jean-Michel (Biological invasions, 2022)
The management of invasive alien species (IAS) is complex and requires consideration of intertwined ecological and economic dimensions. Given the wide variety of costing purposes and practices, and the associated risk of misunderstandings and/or miscommunication which may jeopardize perceptions and management, there is an urgent need to disentangle the nature of IAS costs. We provide a synthesis of the nature and diversity of the economic costs associated with IAS and the potential limits of their assessment. This work promotes a common understanding of costs of IAS across disciplines, which is essential for improving the estimation, interpretation, selection, and uptake of costs when designing IAS management policies or raising societal awareness of their threats. Our study contributes to a clearer understanding of the nature of costs, serving as a sound basis for managing biological invasions.